2006
DOI: 10.1073/pnas.0509972102
|View full text |Cite
|
Sign up to set email alerts
|

PDE1B2 regulates cGMP and a subset of the phenotypic characteristics acquired upon macrophage differentiation from a monocyte

Abstract: Monocyte-to-macrophage differentiation with the cytokine granulocyte-macrophage colony-stimulating factor induces expression of the cyclic nucleotide phosphodiesterase PDE1B2. However, what role PDE1B2 plays in macrophage biology has not been elucidated. We have addressed this question by inhibiting PDE1B2 induction by using RNA interference. Using a retrovirus-based system, we created HL-60 stable cell lines that express a short-hairpin RNA targeting PDE1B2. HL-60 cells treated with phorbol-12-myristate-13-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…We failed to detect PDE1C in mouse peritoneal macrophages and found that PDE1C deficiency does not alter LPS-stimulated cytokine expression in macrophages nor circulating inflammatory molecule levels in mice (our unpublished observations). This is also consistent with the previous findings that the PDE1B isozyme represents the major PDE1 activity in macrophages 62, 63 . Together, these suggest that PDE1C does not regulate macrophage function and systemic inflammation in murine animals.…”
Section: Discussionsupporting
confidence: 93%
“…We failed to detect PDE1C in mouse peritoneal macrophages and found that PDE1C deficiency does not alter LPS-stimulated cytokine expression in macrophages nor circulating inflammatory molecule levels in mice (our unpublished observations). This is also consistent with the previous findings that the PDE1B isozyme represents the major PDE1 activity in macrophages 62, 63 . Together, these suggest that PDE1C does not regulate macrophage function and systemic inflammation in murine animals.…”
Section: Discussionsupporting
confidence: 93%
“…Overall, little is known about regulation of the levels of PDE proteins, although changes in both the activities and levels of particular cGMP-hydrolyzing PDEs have been demonstrated in association with cellular proliferation and differentiation, as well as with tissue dysfunction (Maclean et al, 1997;Kotera et al, 1999a;Palmer and Maurice, 2000;Bender et al, 2004Bender et al, , 2005Champion et al, 2005;Wharton et al, 2005;Bender and Beavo, 2006b;Nagel et al, 2006;Schermuly et al, 2007;Farrow et al, 2008;Miller et al, 2009). Both short-term and long-term regulation of the action of PDEs allows for fine control of the amplitude and duration of cGMP elevation and provides for refined blunting or enhancement of the signal (Gopal et al, 2001;Mullershausen et al, 2001Mullershausen et al, , 2003Rybalkin et al, 2002Rybalkin et al, , 2003Bender et al, 2004Bender et al, , 2005Champion et al, 2005;Takimoto et al, 2005a;Fischmeister et al, 2006;Kass et al, 2007a;Omori and Kotera, 2007;Zhu and Strada, 2007;Muzaffar et al, 2008;Pokreisz et al, 2009;Zhu et al, 2009).…”
Section: Isoenzymementioning
confidence: 99%
“…In cardiac fibroblasts, PDE1A appears to regulate both cGMP and cAMP [19]. PDE1B has been shown to predominantly regulate cGMP levels in macrophages [20], and also appears to play a role in regulating cAMP levels in certain types of cells [21,22]. PDE1C has the highest affinity for cAMP, and appears to regulate cellular cAMP in multiple cell types, including VSMCs [23], βTC3 insulinoma cells, pancreatic islet cells [24], and A172 glioblastoma cells [25].…”
Section: Pde Isozymes In the Heartmentioning
confidence: 99%